The Role of Moving Teachers in Improving the Quality of Education through the Implementation of the Merdeka Curriculum - Wati, Ariesta Dwi Indah Kusuma; Lestari, Neta Dian (PPSDP International Journal of Education, 2025)
This study aims to explore the role of teacher leaders in improving the quality of education through the implementation of the Merdeka Curriculum in Indonesia. The Merdeka Curriculum offers flexibility to teachers and schools to create a contextual and relevant learning process to students’ needs, with a focus on character building and strengthening non-academic skills. The study used a literature study method to examine relevant theories and previous findings. The results of the study indicate that teacher leaders act as agents of change who are able to facilitate educational innovation, improve the quality of learning, and strengthen collaboration between stakeholders. The main challenges in implementing the Merdeka Curriculum include limited infrastructure, teacher readiness in using technology, and students’ socio-economic factors. However, with policy support and collaboration between schools, parents, and communities, teacher leaders can play a crucial role in ensuring that educational transformation is effective. This study provides recommendations for stakeholders to strengthen the Teacher Leader program and increase the success of the implementation of the Merdeka Curriculum.